Teaching emergency ultrasound to emergency medicine residents: a scoping review of structured training methods - Leila L. PoSaw; Brandon M. Wubben; Nicholas Bertucci; Gregory A. Bell; Heather Healy; Sangil Lee (Journal of the American College of Emergency Physicians Open, 2021)
Abstract Background Over the past 2 decades, emergency ultrasound has become essential to patient care, and is a mandated competency for emergency medicine residency graduation. However, the best evidence regarding emergency ultrasound education in residency training is not known. We performed a scoping review to determine the (1) characteristics and (2) outcomes of published structured training methods, (3) the quality of publications, and (4) the implications for research and training. Methods We searched broadly on multiple electronic databases and screened studies from the United States and Canada describing structured emergency ultrasound training methods for emergency medicine residents. We evaluated methodological quality with the Medical Education Research Study Quality Instrument (MERSQI), and qualitatively summarized study and intervention characteristics. Results A total of 109 studies were selected from 6712 identified publications. Publications mainly reported 1 group pretest–posttest interventions (38%) conducted at a single institution (83%), training in image acquisition (82%) and interpretation (94%) domains with assessment of knowledge (44%) and skill (77%) outcomes, and training in cardiac (18%) or vascular access (15%) applications. Innovative strategies, such as gamification, cadaver models, and hand motion assessment are described. The MERSQI scores of 48 articles ranged from 0 to 15.5 (median, 11.5; interquartile range, 9.6–13.0) out of 18. Low scores reflected the absence of reported valid assessment tools (73%) and higher level outcomes (90%). Conclusions Although innovative strategies are illustrated, the overall quality of research could be improved. The use of standardized planning and assessment tools, intentionally mapped to targeted domains and outcomes, might provide valuable formative and summative information to optimize emergency ultrasound research and training.